Covalent Grafting of Coordination Polymers on Surfaces: The Case of Hybrid Valence Tautomeric Interphases. Issue 28 (1st June 2015) - González‐Monje, Pablo; Novio, Fernando; Ruiz‐Molina, Daniel
Abstract We have developed a novel approach for grafting coordination polymers, structured as nanoparticles bearing surface reactive carboxylic groups, to amino‐functionalized surfaces through a simple carbodiimide‐mediated coupling reaction. As a proof‐of‐concept to validate our approach, and on the quest for novel hybrid interphases with potential technological applications, we have used valence tautomeric nanoparticles exhibiting spin transition at or around room temperature. SEM and AFM characterization reveal that the nanoparticles were organized chiefly into a single monolayer while X‐ray photoelectron spectroscopy (XPS) measurements confirm that the nanoparticles retain a temperature‐induced electronic redistribution upon surface anchorage. Our results represent an effective approach towards the challenging manufacture of coordination polymers.